2021
DOI: 10.1108/lht-11-2020-0288
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the behavior of multi-modal information search

Abstract: PurposeWith the increasing abundance of network resources and big data, multi-modal information search (MMIS) has been paid more and more attention, but the research results of MMIS are relatively few. This paper attempts to put forward constructive suggestions for the design of multi-modal information system, so that the system can have a better user experience, help users improve the efficiency of obtaining information and optimize the information service mode.Design/methodology/approachA research model of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…On the other hand, Li et al (2022) presented a study on multi-modal information search (MMIS) and showed that multi-modal information search behavior (MMISB) is directly related to users' search intention, and the search intention can influence users' cognition of the usefulness and ease of MMIS through their information search ability and system characteristics.…”
Section: Faculty Research Characteristics and Information-seeking Beh...mentioning
confidence: 99%
“…On the other hand, Li et al (2022) presented a study on multi-modal information search (MMIS) and showed that multi-modal information search behavior (MMISB) is directly related to users' search intention, and the search intention can influence users' cognition of the usefulness and ease of MMIS through their information search ability and system characteristics.…”
Section: Faculty Research Characteristics and Information-seeking Beh...mentioning
confidence: 99%
“…Therefore, communication is not only carried out by using a single sense but also through multiple senses at the same time. Whether it involves a single medium, dual media, or multimedia, it can be called multimodal if its content is presented in more than one medium (Li et al, 2021). Some scholars believe that compared to pure audio-monomodal materials of the same content, audio-visual materials which involve audio and visual input can reduce the difficulty of listening (Li, 2019).…”
Section: Multi-modalitymentioning
confidence: 99%